KURIKULUM TRIPUSAT PENDIDIKAN DALAM KONTEKS KURIKULUM MERDEKA: PELUANG DAN KENDALA - Alya Nurul Fatwa (JIP: Jurnal Ilmu Pendidikan, 2026)
The concept of the educational tri-center introduced by Ki Hajar Dewantara emphasizes that education occurs within three main environments: family, school, and society. In the implementation of Kurikulum Merdeka initiated by the Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi Republik Indonesia, this concept becomes increasingly relevant. This study aims to analyze the opportunities and challenges of integrating the tri-center education framework within the Merdeka Curriculum. The research employs a qualitative approach using library research and descriptive-analytical methods. The findings reveal that the Merdeka Curriculum is philosophically aligned with the tri-center education concept, particularly through project-based learning and the strengthening of the Pancasila Student Profile. These elements encourage collaboration among families, schools, and communities to support holistic student development. However, several challenges remain, including limited parental involvement, disparities in school resources, and insufficient coordination among educational stakeholders. Strengthening communication and sustainable partnerships is therefore essential to optimize the implementation of the Merdeka Curriculum.